2022
DOI: 10.1155/2022/4070368
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-Sparing Approach in Patients with Endometrioid Endometrial Cancer Grade 2 Stage IA (FIGO): A Qualitative Systematic Review

Abstract: Background. Endometrial cancer (EC) is one of the most common gynecologic malignancy, mostly in postmenopausal women. The gold standard treatment for EC is surgery, but in the early stages, it is possible to opt for conservative treatment. In the last decade, different clinical and pathological markers have been studied to identify women who respond to conservative treatment. A lot of immunohistochemical markers have been evaluated to predict response to progestin treatment, even if their usefulness is still u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 68 publications
(168 reference statements)
0
18
0
Order By: Relevance
“…Information on imaging and physician impression of the masses was also not recorded frequently 10.3389/fmed.2023.1102437 enough to allow meaningful stratification on other diagnostic factors and this may hide interesting interactions in the data. Even though the study did not collect specific information of benign masses, the performance of OvaWatch might support the evaluation of adnexal mass suspicious as endometriosis cysts versus a mass arising from an endometrioid ovarian cancer or metastatic endometrial cancer to the ovary (32,(35)(36)(37)(38)(39) through the testing result of low probability of malignancy versus indeterminate.…”
Section: Discussionmentioning
confidence: 99%
“…Information on imaging and physician impression of the masses was also not recorded frequently 10.3389/fmed.2023.1102437 enough to allow meaningful stratification on other diagnostic factors and this may hide interesting interactions in the data. Even though the study did not collect specific information of benign masses, the performance of OvaWatch might support the evaluation of adnexal mass suspicious as endometriosis cysts versus a mass arising from an endometrioid ovarian cancer or metastatic endometrial cancer to the ovary (32,(35)(36)(37)(38)(39) through the testing result of low probability of malignancy versus indeterminate.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone receptors are more likely present in these well-differentiated tumor cells which leads to a response to progestin therapy [ 2 ]. However, there are no predictive markers of progestogen resistance available at the current time [ 45 ]. The following options are available: LNG-IUS (52 mg) with or without gonadotropin-releasing hormone receptor agonists (GnRH-agonists), oral progesterone such as medroxyprogesterone acetate (400–600 mg/day), or megestrol acetate (160–320 mg/day).…”
Section: Fertility Preservation Treatmentmentioning
confidence: 99%
“…The selection of patients suitable for fertility should be chosen carefully by a comprehensive pretreatment evaluation. Basic requirements for fertility preservation treatment are the absence of a contraindication to medical therapy or pregnancy per se [ 45 ]. Patients with a poorer outcome, itself due to secondary diseases such as other cancers like breast cancer, stroke, deep vein thrombosis, pulmonary embolism or myocardial infarction, a resulting relative or absolute contraindication to hormone therapy as well as a resulting lower successful birth probability, should be advised very critically with regard to fertility preservation [ 18 , 45 ].…”
Section: Fertility Preservation Treatmentmentioning
confidence: 99%
“…Radical surgery and lymphadenectomy are generally recommended for high risk patients. However, the correct selection of patients who might benefit from this kind of treatment is still challenging [7] and, especially when dealing with young patients of reproductive age, fertility sparing approaches need to be considered [8][9][10]. International Federation of Obstetrics and Gynecology (FIGO) stage, histology, depth of myometrial invasion (MI) [7], and lymph node (LN) metastases are the most commonly reported features of EC aggressiveness [11][12][13].…”
Section: Introductionmentioning
confidence: 99%